Use of Writing Strategies in Last Term Engineering Students - Pandal Arenas, Carolina Grimanesa (2020)
This research studies the writing strategies that are most used by students in the last semester of the Engineering degree. Through the cognitive model of Flower and Hayes, and with the application of a survey to these students, several strategies belonging to the planning, translation and revision modules are analyzed. The results indicate that students recognize many of the proposed strategies, but there are still some difficulties that maybe related to an incipient knowledge of academic writing.